PUBLICATIONS OF THE WEEK. (Bookseller, 2003)
Lists various books published in January 2003. 'Little Polar Beer,' by Hans De Beer; 'The Assassination of John F. Kennedy,' by Karen Price Hossell; 'Forest of Doom,' by Ian Livingstone.